One year follow-up results from the Lean Habits Study - Joachim Westenhöfer and T. Klusmann and Astrid Stellfeldt and Carola Strassner and Rudolf Schoberberger and Bernhard Ludvik (2000)
[in International Journal of Obesity, 24 (Suppl. 1), S.171]